NONLINEAR NUMERICAL MODELLING OF BASALT REBAR REINFORCED CONCRETE STRUCTURES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The ever increasing tendency of more complex architecture and increasing use of basalt fibers in concrete, mainly due to corrosion resistance, requires a suitable, accurate and computationally efficient numerical method for modelling of mechanical behavior. A novel numerical modelling methodology for basalt fiber reinforced concrete structures is proposed. In this paper, the main focus is on modelling concrete beams with basalt longitudinal rebars and steel shear rebars. The proposed method is based on two step simulation method. On the first step a database of flexural stiffness depending on stress-strain state is created using non-linear simulations with continuum finite elements. The database of flexural stiffness is used in second step by performing nonlinear beam finite element simulation of frame structures. The numerical method showed good agreement with experimental results. The use of pre-computed database of flexural stiffness significantly accelerate non-linear simulations and whole building can analyzed by taking into account material non-linearity.